Design and Development of Teaching Materials Aimed at Mentor Professional Training - Hašková, Alena; Radulović, Branka; Mikla, Štefan; Stajić, Stefan; Zatkalík, Dominik (Journal of Education Culture and Society, 2023)
Aim. The paper presents information on the concept of teaching materials supporting professional development of mentors, either teacher trainees trainers or introducing teachers of novice teachers, created within an international project by experts from 6 higher education institutions (Constantine the Philosopher University in Nitra – SK, the University of J. Selye in Komárno - SK, Eszterházy Károly Catholic University in Eger - HU, the University of Ostrava in Ostrava - CZ, the Prague University of Economics and Business in Prague - CZ, the University of Novi Sad in Novi Sad – SRB). Methods. Based on analyses of different resources and opinions of experts nominated by the above mentioned higher education institution a mentor competence profile consisting of fifteen key competences was compiled. Based on the platform of the created profile teaching materials supporting successful performance of the mentor role or position were processed. Results. As a main output of the international project 2020-1-SK01-KA201-078250 Mentor training of the Erasmus+ program, five textbooks were created , the basic one in the English version and the other four – its mutations in the national languages of the individual project partners. Conclusion. The textbooks created within the project will be used in the project partner countries within the mentors practical training and preparation. Cognitive value. Currently the concept and philosophy of the teaching materials created within the Mentor training project have become a background for processing further teaching materials supporting mentors´ competence development, which are under preparation within an other international project, namely the bilateral Slovak-Serbian project APVV SK-SRB-21-0025 Mentors´ Vademecum supported by the Slovak Research and Development Agency.